Devising a method for assessing the performance of exergetic efficiency of a pressure wave exchanger - Manoylo, Volodymyr; Korohodskyi, Volodymyr; Voronkov, Oleksander; Avramenko, Andrii; Nikitchenko, Ihor; Shevchenko, Ihor; Iesipov, Oleksandr; Polyashenko, Sergey; Teslenko, Eduard; Lemishko, Daria (Eastern-European Journal of Enterprise Technologies, 2025)
With all their undeniable advantages, forced engines equipped with gas turbine supercharging (GTS) have a significant inherent drawback of the turbocharger (TC), which is associated with the inertia of the TC rotor, causing a discrepancy between the flow characteristics of the supercharger and the hydraulic needs of the engine under transient modes, during sharp acceleration of the vehicle. As an alternative option and one of the effective methods for forcing the engine in order to obtain high technical, economic, and environmental performance indicators of the working process under transient operating modes, a wave pressure exchanger (WPE) is considered as the object of this study. However, the available information related to the energy exchange of working fluids in the units of the wave exchanger has not yet been sufficiently studied. To partially solve this problem, a method has been devised for assessing the exergetic efficiency of WPE, which takes into account the effect of partial exhaust gas recirculation, purging the rotor cells with a fresh charge. Based on the results of development studies, in the presence of a pattern of change in these parameters (purging and recirculation), it is possible to influence the process of improving the working cycle and the exergetic efficiency of the pressure exchanger. A rational combination of purging the rotor cells with a fresh charge (from 4 to 8 %) and reusing part of the combustion products (recirculation from 3 to 5 %) in the working process of the supercharger ensured an increase in the exergetic efficiency of WPE from 0.72 to 0.91 and partially solved the research problem. The resulting data can be implemented both at the early stages of WPE design and for existing modifications of supercharging units, in the process of their further modernization and improvement